(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The article discusses the relevance of vocational guidance of students, the problems arising in this area, and ways to solve them. The requirements for the content of industrial practice and advanced training of students in the field of vocational guidance were discussed.